Bukev (Fagus sylvatica) v jugozahodnem delu Slovenske Istre - nahajališča in fitocenološka oznaka rastišč - Sadar, Zvone (Gozdarski vestnik, 2015)
Based on years of observations we prepared an overview of the beech localities in the southwestern part of Slovenian Istria that are located the closest to the sea. They were found on shady flysch slopes in the elevation belt extending from 68 m to 256 m, in the stands whose tree layer comprises not only beech, but also Quercus pubescens, Q. petraea, Q. cerris, Castanea sativa, Fraxinus ornus, Ostrya carpinifolia, Carpinus betulus and Sorbus torminalis, and which are classified mainly into two associations, Aristolochio luteae-Quercetum pubescentis and Seslerio autumnalis-Fagetum. They are dominated by character species of thermophilous oak forests from the order Quercetalia pubescenti-petraeae, character species of beech forests from the order Fagetalia sylvaticae and character species of oak and beech forests from the class Querco-Fagetea. The species composition of the studied localities confirms that beech used to be more common in this part of Istria than it is today and that its sites on shady aspects were located also in the immediate vicinity of the sea. The existing vegetation maps of forest communities in Slovenian Istria therefore need to be corrected.
Keywords: Fagus sylvatica; fitogeografija; fitocenologija; phytosociology; Aristolochio-Quercetum pubescentis; Seslerio autumnalis-Fagetum; Istra; Istria; Slovenia; Slovenija